Growth, yield and storability of onion varieties as influenced by integrated nutrient management (Bangladesh Journal of Agricultural Research, 2026)
A Field experiment on onion (Allium cepa L.) was conducted at Regional Spices Research Centre, BARI, Gazipur (23059/ North Latitude and 90024/ East Longitude) during rabi season of 2021-2022 and 2022-2023. The objectives were to find out promising onion variety, to develop a balanced nutrient management package for higher bulb yield with longer storability and to make a nutrient balance sheet for revealing the condition of soil fertility. The experiment was designed in Factorial Randomized Complete Block Design having three replications and nine treatments comprising three winter onion varieties: BARI Piaz-1 (V1), BARI Piaz-4 (V2) and BARI Piaz-6 (V3) and three nutrient management packages i.e., 100% RDF (120-60-100-20-3-1.5 kg NPKSZnB ha-1) + Cowdung @ 5 tha-1 (N1), 100% RDF + Vermicompost @ 3 t ha-1 (N2) and 100% RDF + Poultry manure @ 3 t ha-1 (N3) kg ha-1. The highest bulb yield (30.65 and 32.06 t ha-1), marketable bulb yield (29.24 and 31.03 t ha-1) was recorded from var. BARI Piaz-4 cultivated with 100% RDF + Vermicompost @ 3 t ha-1 in both the year. The net nutrient balance of N (-38 to -146 kg ha-1), K (-10.92 to -21.06 kg ha-1) and S (-0.70 to -2.68 kg ha-1) showed negative balance but P (0.3 to 0.8 kg ha-1) was positive. The highest total physiological loss of weight (PLW) of onion (19.5 and 21.7% in both the year) was recorded when onion var. BARI Piaz-6 was fertilized with 100% RDF + Poultry manure @ 3 t ha-1 during 120 days of storage. Among the onion varieties, BARI Piaz-6 was more susceptible to PLW. Hence, BARI Piaz-4 appeared as high yield potential onion variety and a combination of 120-60-100-20-3-1.5 kg NPKSZnB ha-1 + Vermicompost @ 3 t ha-1 was found to be the most suitable package in augmenting yield and sustaining soil health in the studied location of Madhupur Tract (AEZ-28).Bangladesh J. Agril. Res. 49(1): 43-55, March 2024